Authoritarian conflict management in post-colonial Eurasia. Issue 3 (4th May 2019) - Heathershaw, John; Owen, Catherine
ABSTRACT: This contribution considers 'illiberal peace' in post-colonial Eurasia in the aftermath of the Soviet Union and in the shadow of Russia and China as 'emerging powers'. Authoritarian modes of conflict management – which have economic, spatial and discursive aspects – are oriented towards regime consolidation and the creation of a particular type of political economy. We should understand these as a form of authoritarian interventionism which had three main goals in this context: (1) to end violence conflict by preventing rebels from influencing public discourse; (2) to control the resources; and (3) to shape the political space. Despite the fact that liberal actors do illiberal things, and vice versa, this contribution argues that in order for this complexity to make political sense the distinction between liberal and illiberal should be maintained. Furthermore, in order for these illiberal practices to make historical sense we must situate them in their regional, colonial and post-colonial contexts.